Network Analysis: Climate Security Observatory - Craparo, Alessandro Carmelo William; Basel, Ashleigh Megan; Minoarivelo, Henintsoa Onivola (2023)
The Climate Security Observatory (CSO) is an online platform for stakeholder decision-making that provides access to a range of global analyses related to climate and security. The CSO is based on an integrated climate security framework that helps understand the complexity of the climate-security interface. As part of the CSO Methods Paper Series, this report details the method used for the Network Analysis.